2020
DOI: 10.3390/cells9102318
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA Profile in Non-Hodgkin’s Lymphoma Patients with Secondary Myelodysplasia

Abstract: Myelodysplastic syndromes are a group of clonal diseases of hematopoietic stem cells and are characterized by multilineage dysplasia, ineffective hematopoiesis, peripheral blood cytopenias, genetic instability and a risk of transformation to acute myeloid leukemia. Some patients with non-Hodgkin lymphomas (NHLs) may have developed secondary myelodysplasia before therapy. Bone marrow (BM) hematopoiesis is regulated by a spectrum of epigenetic factors, among which microRNAs (miRNAs) are special. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Normally, only about 200 miRNAs are expressed at sufficiently high levels, with some of them varying between the samples and the others being invariant. The authors of all publications about NanoString-based miRNA quantification data are largely interested in finding the most significant differences in miRNA expression levels between the groups [ 22 , 23 ]. By contrast, we wanted to find those miRNAs that have stable expression in all groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, only about 200 miRNAs are expressed at sufficiently high levels, with some of them varying between the samples and the others being invariant. The authors of all publications about NanoString-based miRNA quantification data are largely interested in finding the most significant differences in miRNA expression levels between the groups [ 22 , 23 ]. By contrast, we wanted to find those miRNAs that have stable expression in all groups.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, when we were deciding on the reference gene for analysis of miRNA expression levels in bone marrow samples, we used NanoString nCounter and chose the geometric mean of the expression levels of miR-378 and miR-191. Analysis of miRNA quantification data obtained with NanoString nCounter showed that the abundance of these miRNAs in the samples was well above background values, but these miRNAs had the least variable expression across the groups [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular genetic markers are gradually becoming more and more popular in describing MDS; in addition, they discriminate MDS from other BM conditions [ 109 , 110 , 111 , 112 , 113 ]. As described above, unique miRNA expression profiles are characteristic of different MDS subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…NanoString-based miRNA quantification data are largely interested in finding the most significant differences in miRNA expression levels between the groups [22,23]. By contrast, we wanted to find those miRNAs that have stable expression in all groups.…”
Section: Discussionmentioning
confidence: 99%